Insomnia symptom severity is associated with increased suicidality and death by suicide in a sample of patients with psychiatric disorders. Issue 7 (11th February 2021) - Simmons, Zach; Burlingame, Gary; Korbanka, Juergen; Eastman, Kevin; Thomas, Douglas; Christensen, Jeremy; Jenson, Michelle; Nadorff, Michael R; Kay, Daniel B
Abstract: Study Objectives: Insomnia is a risk factor for suicidal behavior including attempts and death by suicide. We investigated whether insomnia symptom severity was associated with suicidality and death by suicide in patients with psychiatric disorders. Methods: The sample included 180 deceased patients with psychiatric disorders seen at Weber Human Services between 2008 and 2018 who completed the Outpatient Questionnaire-45.2 (OQ) prior to death. Insomnia symptom severity was assessed using item 41 from the OQ. Manner of death was determined by death records and autopsy reports. History of suicidality was determined through electronic medical records. Cases were grouped into four lifetime categories: non-suicidal ( n = 30), suicidal ideation ( n = 36), suicide attempt ( n = 95), and death by suicide ( n = 19). Demographic, medical, and psychiatric features of each group were compared using linear regression. Logistic regression was used to determine whether insomnia symptom severity was associated with lifetime suicidality severity grouping, adjusting for psychiatric disorders commonly linked to suicidality. Results: Lifetime suicidality was associated with sleep problems, fatigue, headaches, and psychiatric disorders (i.e. depressive, personality, and trauma-related disorders). Referenced to the non-suicidal group, greater insomnia symptom severity was significantly associated with suicide attempts and death by suicide, with odds ratios (OR) of OR = 2.67, p = 0.011, and OR = 5.53, p = 0.002, respectively, even after adjusting important psychiatric diagnoses. Conclusions: Results suggest that insomnia symptom severity endorsed during a clinical visit is associated with heightened suicidality, especially suicidal behavior. The presence of insomnia symptoms in patients with psychiatric disorders may indicate risk for suicide and is a target for suicide prevention.